A comparative clinical study on use of isoflurane and sevoflurane anaesthesia following dexmedetomidine premedication and propofol induction in dogs - R., Akarsh; Reddy, Jagan Mohan; T., Madhav Rao; E.L., Chandra Shekhar; N., Rajendranath (Indian Journal of Veterinary Surgery, 2026)
The objective of the study was to compare isoflurane and sevoflurane inhalation anaesthesia in dogs premedicated with dexmedetomidine and anaeshesia induced with propofol. The study was conducted in 12 dogs, divided in two equal groups, I and II, undergoing various orthopaedic procedures. All the animals of two groups were premedicated with dexmedetomidine (20 µg/kg body wt, i.v.) 15 min before induction of anaesthesia with propofol (3 mg/kg body wt, i.v.). Anaesthesia was maginated by isoflurance in group I and Sevoflurans in group II. There was a significant decrease in rectal temperature and respiratory rate and no change in heart rate during anaesthesia in both groups. Haemoglobin, PCV and TEC values did not change significantly, while TLC values showed a significant decrease in both groups. Serum creatinine and BUN levels were significantly decreased in both groups; however, ALT and AST levels were within the normal physiological range. No arrhythmia was recorded in both groups. In group I, the mean duration (in min) of extubation time, sitting time and complete recovery of animals were 8.73±0.34, 16.13±0.23 and 21.97±0.43, min, respectively. In group II, the values were 5.10±0.24, 9.37±0.23 and 15.47±0.17 min, respectively. Regaining of the reflexes in group II was faster than group I. Both isoflurane and sevoflurane provided excellent anaesthesia and recovery characteristics; however, sevoflurane had faster recovery compared to isoflurane.